IOT based Smart weighing system for Crate in Agriculture - Sonsare, PM (International Journal of Computer Sciences and Engineering, 2025)
As people are getting smarter so are the things. The Internet of Things (IoT) is a system of connecting mechanical and digital machines, animals or people with interrelated computing devices to provide an ability to collect process and transfer data over a network without requiring human interaction. While the thought comes up for smart cities there is a requirement for smart agriculture. As an example, this project presents a Smart weighing system which can be used for agriculture automation. The idea of Smart weighing system is for the farmer where they can weight their goods by placing it in crate. The Smart weighing system thus thought is an improvement of normal weighing machine by elevating it to be smart using sensors and logics. Smart weighing machine is a new idea of implementation which makes a normal weighing machine smart using sensors for weighing goods and sending message to keep track of the container using GSM modem.